Oral Health, Antimicrobials and Care for Patients With Chronic Oral Diseases - A Review of Knowledge and Treatment Strategies - Mark Ide; Malika Karimova; Jane Setterfield (Frontiers Media S.A., 2022)
Periodontal and chronic oral mucosal diseases are significant life impacting conditions which may co-exist and synergistically act to cause more severe and widespread oral pathology with enhanced challenges in effective management. Clinicians regularly observe these effects and struggle to effectively manage both problems in many patients. There is limited understanding of many basic and applied scientific elements underpinning potentially shared aetiopathological features and management. Recent developments in translational science provide an opportunity to greater improve knowledge and subsequently care for patients with these problems.